Consciousness and the nonhuman: the imaginary of the new brain sciences in Ian McEwan's Nutshell and Machines Like Me. Issue 3 (4th March 2022) - Colombino, Laura
ABSTRACT: The article sketches the philosophical theories of consciousness of the 2010s inspired by neuroscience and computer science, in order to relate them to Ian McEwan's investigation of a protohuman and a posthuman mind, those of a foetus and a robot, in Nutshell and Machines Like Me respectively . McEwan engages inventively with the contemporary imaginary of the new brain sciences and tries to make sense of the increasingly blurred boundaries between the human and the nonhuman, by revisiting the theme of the emergence of consciousness found in Frankenstein. Human consciousness is shown as poised ontogenetically and phylogenetically between two nonhuman states: its origin in neurobiological substance and its possible final dissolution into digital matter. McEwan affirms the importance of human agency in the face of the determinisms of biology and algorithm, and asserts the idea that the mind is shaped by narrative, against the reductionisms of biogenetic and algorithmic materialisms. He also challenges transhumanist visions, by showing that the beauty of human imperfection lies in pleasure, playfulness, and the endless dilemmas of the soul. Finally, the article considers the way in which Nutshell and Machines Like Me engage with collective consciousness and discusses their ethical message for the twenty-first century reader.